2003
DOI: 10.1074/jbc.m304043200
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Lipid A Species Modified with 4-Amino-4-deoxy-l-arabinose in Polymyxin-resistant Mutants of Escherichia coli

Abstract: ArnB was overexpressed using a T7lac promoter-driven construct and shown to catalyze the reversible transfer of the amino group from glutamate to the acceptor, uridine 5-(␤-L-threo-pentapyranosyl-4؆-ulose diphosphate), the intermediate that is synthesized by ArnA from UDPglucuronic acid. A 1.7-mg sample of the putative UDP-LAra4N product generated in vitro was purified by ion exchange chromatography, and its structure was confirmed by 1 H and 13 C NMR spectroscopy. ArnB, which is a cytoplasmic protein, was pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
129
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 110 publications
(134 citation statements)
references
References 42 publications
(104 reference statements)
4
129
1
Order By: Relevance
“…The forward typhimurium, biosynthesis of the L-Ara4N moiety begins with oxidation of UDP-glucose to UDP-glucuronic acid (2). Next, the C-terminal domain of ArnA catalyzes the NAD ϩ -dependent oxidative decarboxylation of UDP-glucuronic acid to yield an unusual UDP-4-ketopentose (30,32), which is converted by the transaminase ArnB to UDP-␤-L-Ara4N (29). Subsequently, the N-terminal domain of ArnA uses N-10-formyltetrahydrofolate to N-formylate UDP-␤-L-Ara4N (28,30,32).…”
Section: Methodsmentioning
confidence: 99%
“…The forward typhimurium, biosynthesis of the L-Ara4N moiety begins with oxidation of UDP-glucose to UDP-glucuronic acid (2). Next, the C-terminal domain of ArnA catalyzes the NAD ϩ -dependent oxidative decarboxylation of UDP-glucuronic acid to yield an unusual UDP-4-ketopentose (30,32), which is converted by the transaminase ArnB to UDP-␤-L-Ara4N (29). Subsequently, the N-terminal domain of ArnA uses N-10-formyltetrahydrofolate to N-formylate UDP-␤-L-Ara4N (28,30,32).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to their function as a key member of the innate immune system, CAMPs represent an important class of clinical antimicrobials. They have both intrinsic bactericidal activity and appear to enhance the activity of other antibiotics, presumably by facilitating their entry into the microbe (3,10,11 21). The N-terminal domain (residues 1-313) is similar in sequence to other enzymes involved in formyl transfer.…”
mentioning
confidence: 99%
“…All of these gene products except pmrM are essential for the biosynthesis of Ara4N-lipid A and for resistance to CAMPs (18). In vitro studies by Raetz and co-workers have shown a pathway for the biosynthesis of UDP-L-Ara4N from UDP-glucose (UDP-Glc) (19)(20)(21). The pathway begins with the oxidation of UDP-Glc to UDP-glucuronic acid (UDP-GlcA) catalyzed by the well-characterized UDP-Glc dehydrogenase (PmrE/Ugd) ( Figure 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on its homology to yeast dolichyl-phosphate mannose synthase, E. coli PmrF was postulated to be involved in the synthesis of the lipid-linked L-Ara4N donor (58). In fact, PmrF (ArnC) catalyzes the selective transfer of L-Ara-formyl-4N from UDP-N-formyl-4-amino-4-deoxy-L-arabinose to undecaprenyl phosphate, generating a lipid precursor that is immediately deformylated by ArnD (59,60). The final lipid donor, undecaprenyl phosphate-␣-L-Ara4N, isolated in milligram quantities from the lipid fraction of polymyxin-resistant mutants, is well characterized (35).…”
Section: Discussionmentioning
confidence: 99%